Comparison of executive functions with borderline intellectual functioning, attention deficit hyperactivity disorder and healty groups using the event-related potentials method - DURU, ADİL DENİZ (My University, 2021)
Objective: In this study, it will be evaluated whether there is a difference in executive function performances between individuals with Attention Deficit Hyperactivity Disorder (ADHD) and those with Borderline Intellectual Functioning, and to what extent this difference differs from the healthy group. In addition, by evaluating the executive functions of all three groups through Event-Related Potentials, it will be investigated whether there is a difference in the electrical waves obtained between the three groups and how the deterioration in executive functions is reflected on the electrical waves. Methods: Between the ages of 10-18, who applied to the Outpatient Clinic of Atatürk University Faculty of Medicine Department of Child and Adolescent Psychiatry and Diseases, 20 individuals diagnosed with ADHD, 20 individuals diagnosed with Borderline Intellectual Functioning, and 20 age-matched healthy individuals with the study group were included in the study. In the study, sociodemographic data form and Developmental and Mental Health Assessment (DAWBA) were applied, and DSM-V based clinical interviews were conducted. ADHD was diagnosed with DAWBA. In the study, only individuals with no loss of intellectual functioning who were diagnosed with Oppositional Defiance disorder were included in the diagnosis of ADHD as a comorbid. The group diagnosed with Borderline Intellectual Functioning; It consisted of individuals who had an IQ between 70-85 as a result of the WISC-R Intelligence Test (Wechsler Intelligence Scale for Children) who did not have any psychopathology. In order to evaluate executive functions, Stroop task was applied, and electrical activity in the brain was recorded through Event-Related Potentials (ERP) during the test process. The Stroop material was created in the computer environment using the MATLAB program within the scope of the study. Before starting the Stroop task, baseline EEG was recorded for 45 seconds. There were 5 sessions in the Stroop task and 15 stimuli were shown in each session. These 15 stimuli are the stimuli on which the colors "Red", "Blue", "Yellow", "Green" are written. The subject is asked to press the left button of the mouse when the stimulus that is compatible with the color name written on the screen comes (compatible stimulus), and not to press the left button of the mouse when the stimulus that is incompatible with the color name written on the screen comes (incompatible stimulus). 70% of the stimuli are compatible and 30% are incompatible. After 5 sessions of the Stroop task were completed, a 45-second baseline EEG was recorded again. Total Stroop task time is approximately 8 minutes. Obtained behavioral parameters; Total of correct response, Correct response latency (reaction time), Total of incorrect response, Incorrect response latency, commission error and omission error. The data obtained from the research were evaluated using the SPSS (The Statistical Package for Social Sciences) 24.0 package program. Statistically p<0.05 values were considered significant. Results: In the sample of our study; while 5 (25%) of the ADHD group were girls, 15 (75%) were boys and the mean age was 12 (12.5 ± 2). While 11 (55%) of the Borderline Intellectual Functioning group were girls and 9 (45%) ) was male and the mean age was 12 (12.2 ± 1.4). The mean age was 12 (12.3 ± 2) in the control group, with 10 girls (50%), 10 boys (50%). There was no statistically significant difference between the three groups in terms of gender distribution and mean age. As a result of DAWBA for all three groups; There was no psychiatric comorbid condition in the ADHD group. Correct reaction times on the Stroop task were found to be statistically significantly longer in individuals with a diagnosis of borderline intellectual functioning than in the other two groups. In individuals diagnosed with ADHD, the number of comission error was found to be statistically significantly higher. In individuals diagnosed with Borderline Intellectual Functioning, a statistically significant difference was found between the number of correct, wrong numbers and omission error in the Stroop task compared to the control group. In our study, the amplitude of the P300 electrical wave obtained by ERP during the Stroop task, in which executive functions were evaluated, was found to be statistically significantly higher in individuals with borderline intellectual functioning compared to the other two groups. Discussion: In the Stroop task, individuals with ADHD were found to have significant performance impairment compared to the other two groups in behavioral data related to possible inattention and impulsivity symptoms. In the literature, commission error has been found to be associated with impulsivity (1). In this context, it was thought that impulsivity being the main symptom of ADHD may have contributed to the results obtained. The Stroop task is a test that evaluates cognitive capacity as well as attention (2). In the Stroop task, performance impairment was found in behavioral data thought to be related to the cognitive capacities of individuals diagnosed with Borderline Intellectual Functioning. It was thought that the long reaction time obtained in our study may be related to the slow processing speed of individuals with borderline intellectual functioning. In addition, an increase in amplitude was observed in our study, which supports the long reaction time and cognitive slowness. In the literature, it is stated that individuals with borderline intellectual functioning have a slower processing speed than individuals with normal cognitive development (3).
Keywords: ADHD; Borderline Intellectual Functioning; Event-related potentials; Stroop task; executive functions